Analysis of Return on Asset, Return on Equity and Earnings Per Share on Stock Prices in Banking Sector Companies in 2019-2023 - Imeliyanti, Eka; Indrawati, Dwi Rizqiani; Anwar, Moh Nuril; winanti, winanti; Goestjahjanti, Francisca Sestri; Sopyan, Dedi; Hasna, Shoftwatun; Singgih, Eman; Farhan, Akhmad (Journal of E-business and Management Science, 2024)
The investment trend in Indonesia is starting to increase, making many people want to try to start investing, but if this desire is not based on understanding it will lead to high risks. This research aims to determine the factors that can influence the movement of share prices, especially fundamental analysis, namely analysing financial reports to determine the financial performance of companies in the banking sector that have high market capitalization in Indonesia. By measuring Return on Assets (ROA), Return on Equity (ROE) and Earning Per Share (EPS), whether the variables in this research influence stock market prices. By using SPSS to process data and produce conclusions. Based on the results of this research, it is stated that the variables X1 (ROA) and X3 (EPS) have a partially significant effect on share prices, in contrast to the variable So, prospective investors who want to start investing should look at the company's financial reports first, especially analysing the assets, net profit and profits generated by the company